Association of Pre-stroke Frailty With Prognosis of Elderly Patients With Acute Cerebral Infarction: A Cohort Study - Yang, Fuxia; Li, Nan; Yang, Lu; Chang, Jie; Yan, Aijuan; Wei, Wenshi (Frontiers in Neurology, 2022)
Background: Frailty is a state of cumulative degradation of physiological functions that leads to adverse outcomes such as disability or mortality. Currently, there is still little understanding of the prognosis of pre-stroke frailty status with acute cerebral infarction in the elderly. Objective: We investigated the association between pre-stroke frailty status, 28-day and one-year survival outcomes, and functional recovery after acute cerebral infarction. Methods: Clinical data were collected from 314 patients with acute cerebral infarction aged 65-99 years. A total of 261 patients completed follow-up in the survival cohort analysis and 215 into the functional recovery cohort analysis. Pre-stroke frailty status was assessed using the FRAIL score, prognosis was assessed using the modified Rankin Scale (mRS), and disease severity using the National Institutes of Health Stroke Scale (NIHSS). Results: Frailty was independently associated with 28-day mortality in the survival analysis cohort (HR=4.30, 95% CI 1.35-13.67, p=0.014). However, frailty had no independent effect on one-year mortality (HR=1.47,95% CI 0.78-2.79, p=0.237), but it was independently associated with advanced age, severity of cerebral infarction, and combined infection during hospitalization. Logistic regression analysis after adjusting for potential confounders in the functional recovery cohort revealed frailty and NIHSS score were significantly associated with post-stroke severe disability (mRS> 2) at 28 days (pre-frailty aOR: 8.86, 95% CI 3.07-25.58, p <0.001; frailty aOR: 7.68, 95% CI 2.03-29.12, p=0.002) or one year (pre-frailty aOR: 8.86, 95% CI 3.07-25.58, p <0.001; frailty aOR: 7.68,95% CI 2.03-29.12, p=0.003). Conclusions: Pre-stroke frailty is an independent risk factor for 28-day mortality and 28-day or one-year severe disability. Age, NIHSS score, and co-infection are likewise independent risk factors for one-year mortality.